CRISPR/dCas12a-mediated activation of SlPAL2 enhances tomato resistance against bacterial canker disease - Diana Marcela Rivera-Toro; Stefan de Folter; Raúl Alvarez-Venegas (PLoS ONE, 2025)
Crop protection is essential for maintaining and improving agricultural productivity. While pesticides are commonly used to control pests, they pose several challenges, including environmental harm and health risks. Alternative strategies to pesticides include breeding resistant crop varieties, biological control, and utilizing genome-editing tools like CRISPR/Cas. However, the application of epigenome editing, particularly CRISPR activation (CRISPRa), in plants remains underexplored. Phenylalanine ammonia-lyase (PAL), a key enzyme in the phenylpropanoid pathway, plays a pivotal role in plant defense by producing lignin and other secondary metabolites essential for pathogen resistance. In this study, we engineered tomato plants by fusing the SET-domain of the SlATX1 coding gene, a histone H3 lysine 4 tri-methyltransferase, to dCas12a, targeting the SlPAL2 promoter with the aim to increase PAL2 gene expression. CRISPRa-edited plants demonstrated increased deposition of the H3K4me3 epigenetic mark and significantly upregulated SlPAL2 expression. This enhanced lignin accumulation and conferred increased resistance to Clavibacter michiganensis subsp. michiganensis (Cmm) without significant reduction in plant height or fruit yield. Disease resistance was also associated with reduced pathogen load and lesion size, and higher lignin levels persisted even after SlPAL2 expression declined post-infection. These findings highlight the potential of CRISPRa for reprogramming plant defense responses through targeted histone modifications, offering a sustainable approach for crop improvement. Furthermore, CRISPRa could also be applied to enhance crop resilience in other contexts, such as addressing food security challenges by enhancing productivity.